Trends and Developments in Online Collaborative Writing: A Bibliometric Review - Ramadhani, Dian Puspita; Ayuba, Hasan (English Education Department, 2023)
The digital era has revolutionized educational practices, with online collaborative writing emerging as a pivotal approach in fostering student engagement, critical thinking, and communication skills. This bibliometric study aims to analyze the trends and developments in research on online collaborative writing over the past decade, highlighting key contributions, research methodologies, and thematic focuses within the field. By employing bibliometric tools such as VOSviewer and Bibliometrics, the study examines publications from leading academic databases, offering insights into the evolution of this pedagogical method. The findings reveal significant growth in the number of studies, with a particular surge during the COVID-19 pandemic. The analysis also uncovers a predominance of quantitative research designs, particularly quasi-experimental studies, while identifying gaps in qualitative research. This review provides a comprehensive overview of the current state of online collaborative writing research, suggesting future directions for investigation and emphasizing the relevance of this practice beyond educational settings in an increasingly digital and collaborative world.